2020
DOI: 10.3390/eng2010001
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Techniques in the Context of Actions for Flood Risk Management: A Review

Abstract: The general purpose of this review paper is to provide an overview of various flood protection strategies because flooding is becoming more frequent and is affecting more areas, displacing people, and increasing fatalities around the world. The concern surrounding climate change resulting in sea level rise, increasingly frequent storm events, and the need for adaptive actions to better control urban storm water runoff motivates the completion of this paper. Understanding the impact of climate change aside from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…These studies highlight the benefits of TWW irrigation in terms of nutrients supply but do not investigate aspects relating to TWW production. Traditional grey infrastructures, mostly based on concrete, have been largely used to obtain TWW over time but their efficiency has been not always high mainly due to economic and technological reasons [43]. In this context, in many arid and semi-arid regions of the world, CWs contribute to the integrated water management, can efficiently purify various type of wastewater and provide TWW for irrigation purpose in accordance with sustainability criteria.…”
Section: Plos Onementioning
confidence: 99%
“…These studies highlight the benefits of TWW irrigation in terms of nutrients supply but do not investigate aspects relating to TWW production. Traditional grey infrastructures, mostly based on concrete, have been largely used to obtain TWW over time but their efficiency has been not always high mainly due to economic and technological reasons [43]. In this context, in many arid and semi-arid regions of the world, CWs contribute to the integrated water management, can efficiently purify various type of wastewater and provide TWW for irrigation purpose in accordance with sustainability criteria.…”
Section: Plos Onementioning
confidence: 99%
“…The deteriorating conditions of the watercourses, gates, and drainage outlets result in low performance and water losses. The government needs to pay attention to the delayed maintenance, and a shortage of rehabilitation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, a resilient flood risk management strategy focuses on reducing the impacts of floods via efficient warning systems, evacuation plans, building regulations in flood-prone areas, and the applications of spatial planning [15,16]. Hampering of floods is difficult, but damages and exposure of flooding to risk-lain communities can be minimized with flood risk management [15,[17][18][19][20]. Additionally, there has been a change from structural flood protection measures towards resilient or integrated flood risk management over the past ten years as many studies have revealed that communities adapted to shocks and disturbances rather than resistance are more durable [21].…”
Section: Introductionmentioning
confidence: 99%
“…As efforts to reduce the frequency of occurrence and lessen impacts of flood disasters in many susceptible areas intensify, more methods of flood vulnerability and flood risks assessments have emerged over the decades (Perera et al, 2019;Martinez et al, 2021). Flood risk evaluation or vulnerability assessment has been described as the proactive steps for preventing flood disasters and to provide guidance for mitigation decisions (MRC, 2016;Tascón-González et al, 2020).…”
Section: Introductionmentioning
confidence: 99%